AN ECONOMIC ANALYSIS OF THE EFFECT OF SOME ECONOMIC VARIABLES ON THE STRUCTURE OF AGRICULTURAL EMPLOYMENT IN IRAQ FOR THE PERIOD 1990-2017 - & Al-Hiyali, Alsudani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The research aimed at analyzing the structure of agricultural employment in Iraq as well as analyzing the current status of economic variables related to agricultural employment during the period 1990-2017, including the agricultural workforce, agricultural wages, agricultural investment and agricultural GDP. In the achievement of its objectives, the research relied on descriptive and quantitative analysis, as well as the use of some modern econometric  methods in estimating models. The results using the ARDL methodology in the analysis indicate a long-term relationship between the volume of agricultural employment and each of the explanatory variables included in the model, which are (agricultural GDP, agricultural investments, agricultural wages and technological development). The research concluded that the negative effects of the policies pursued towards the agricultural sector to a large extent have been reflected on the size of the demand for agricultural employment and the productive efficiency of agricultural labor. The research recommended that investments should be directed to developing human resources, aiming to raise their efficiency, and encouraging the private sector to increase investments in various fields that would open new labor markets in order to accommodate the various types of unemployment that exist in the state’s economic structure.